Study of the Distribution of River Beaver (Castor fiber) in the Liuoba and Guntinas Rivers - Lukošienė, Daiva (Jaunųjų mokslininkų darbai, 2024)
River beaver’s (Castor fiber) lifestyle and ability to survive influence nature ecosystems. Beavers in their living environment raise the water level and thus flood areas of forest and land. This paper analyzes the results obtained from the assessment of river beaver habitats in two rivers with different water discharges. The study to determine the activity of beavers and their impact on the environment was carried out in October-November 2023. Active beaver sites were determined by fresh crawl paths and fresh tree bites. There are two types of beaver biotopes in the territory of north-western Lithuania chosen for the study: large and small natural rivers. The monitoring of beaver sites was carried out by investigating the studied area along Luoba – a large natural river and Guntinas – a small natural river.The number of beavers hunted in Skuodas district is 3.4% of Lithuania. During the examination, fourteen beaver sites were discovered, which were located in beds of Luoba and Guntinas rivers. There were 60% more beavers in the Guntinas than in Luoba. The average distance between active beaver sites is 279 meters. During the study, after counting the gnawed woody plants near the beaver habitats, the main plants used in beaver’s diet were identified: willow (30%), aspen (21%), and birch (18%).
Keywords: Skuodas district; beaver biotopes; beaver nutrition